Makna Simbol-Simbol dalam Tradisi Hamis Batar (Syukur Jagung) pada Suku Tetun Desa Wehali Kecamatan Malaka Tengah Kabupaten Malaka - Remigius F. Fouk; Blajan Konradus; Yohanes K. N. Liliweri (Universitas Nusa Cendana, 2019)
Meaning of Symbols in the Tradition of Hamis Batar (Gratitude of Maize) On the Suku Tetun of Wehali Village, Malaka Tengah Sub-district, Malaka Regency. (Culture society of Malaka Regency have a set of meaning value system.,The system is manifested in the structure and the social patterns that are implemented in accordance with the standards passed down from generation to generation. The meaning is contained in